Залежність водного режиму інтродукованих лісових рослин від їх біологічної активності - Kovalenko, E.A.; Kaspari, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
Dependence of water regime on accumulation of biologically active matters was studied. In plantations where Pinus sylvestris privails was found higher water deficiency than in plantations with dominating foliage species.